Open SkyQuery - VO Compliant Dynamic Federation of Astronomical Archives - Budavari, Tamas; Szalay, Alex S.; Malik, Tanu; Thakar, Ani; O'Mullane, William; Williams, Roy; Gray, Jim; Mann, Robert; Yasuda, Naoki (Astronomical Data Analysis Software and Systems XIII, ASP Conference Series, 2003)
We discuss the redesign of the SkyQuery architecture, originally built as a simple proof of concept for dynamic federation of astronomical archives. In keeping with the Virtual Observatory philosophy of hierarchical services, the design of Open SkyQuery is based upon higher level services extending the basic functionality of the current VO standard, the ConeSearch. Open SkyQuery implements the VO specifications for data access, retrieval and spatial join. Data are published via Web Services called SkyNodes providing a rich functionality including footprint coverage. SkyNodes are discovered through the VO registry. We propose to have at least two levels of SkyNode compliance (Basic and Full). We will also provide templates for publishing data into a SkyNode.